Velocity overshoot within the accelerated subsonic boundary layer over the heated wall. (November 2020) - Sakhnov, A.Yu.; Naumkin, V.S.
Highlights: Velocity overshoot may exist in the compressible flow with both laminar and turbulent regimes. Compressibility has a weak effect on the overshoot magnitude. In the compressible boundary layer the overshoot has less effect on the skin-friction than in the low speed flow. Mach number distributions have not any maximal values within the boundary layer. Abstract: The paper presents results on the numerical investigation of the accelerated compressible flow near the hot surface with constant heat flux. Such conditions may generate a phenomenon of the overshoot, when the streamwise velocity within the boundary layer is higher than the velocity of the main flow. We simulated properties of helium-xenon mixture and superheated water vapor. Numerical model consist of the system of Prandtl equations, which describe dynamic and thermal processes in the boundary layer, and k-ω-γ turbulence model that allows simulate reasonably as turbulence as laminar-turbulent transition. Finite difference methods were applied for solving of differential equations. The numerical model was able to block artificial the term of viscous dissipation in the energy equation and set a constant temperature at the outer border of the boundary layer in order to evaluate the effect of compressibility on the overshoot phenomenon and other flow characteristics. It is shown that the unambiguous relationship between skin friction coefficient and the overshoot magnitude is violated for Mach number from 0.4 to 1.0. Maximal values are disappeared at representation of velocity through Mach number.